Genre Based Approach: A Way to Enhance Students’ Writing Ability - Irawansyah, Irawansyah (English Education: Jurnal Tadris Bahasa Inggris, 2016)
The goal of this research is to know whether genre based approach is able to enhance student’s writing ability. The research was conducted towards students of English education department which consists of 26 students. The method of this research is classroom action research which applies two cycles. Each cycle covered five stages, namely planning, implementing, observing, and reflecting. In addition, test, observation, interview, and field note were used to collect the data. After collecting the data, the data were analyzed by using descriptive statistics (quantitative) and data reduction, data display, and conclusion (qualitative). The research finding shows that the students’ writing ability underwent the improvement from 56.56 to 68.52. Therefore, it can be concluded that genre based approach is able to enhance students’ writing ability.